THE OBSTACLES IN ONLINE LEARNING OF ENGLISH EDUCATION STUDENTS ACADEMIC YEAR 2017 DURING COVID-19 PANDEMIC - Emilia Widiyanti; Mohammad Amiruddin (The Ellite of Unira, 2022)
Covid-19 makes learning activities must be carried out online in order to break the chain of the spread of covid-19. This study aims to find out what obstacles and effects students face during their online learning using qualitative research methods. The subjects of this study were students of the 7th semester of English education study program totalling 6 people using questionnaires and interview data collection techniques. To collect research results on the questionnaire using tables and for interviews using analytical techniques. The results of the research on the questionnaire were 40% of students answered that they had problems with the network and 60% experienced problems with the lecturer's explanation. on the effect of online learning students answered that they experienced the effect that they were more lazy since joining online learning, the next effect their scores increased during online learning. This shows that during online learning they have obstacles and effects that they face during online learning and it is recommended for lecturers to pay more attention to students who have difficulty in capturing material during online learning so that they are more enthusiastic about participating in online learning.